2018
DOI: 10.14712/23363177.2015.83
|View full text |Cite
|
Sign up to set email alerts
|

Case-Based Learning in Initial Teacher Education: Assessing the Benefits and Challenges of Working with Student Videos and Other Teachers’ Videos

Abstract: Abstract:The ability to analyze classroom situations proficiently is regarded as one of the key prerequisites for successful teaching. Although a steadily increasing body of empirical evidence proves that case-based learning with videos can foster professional vision in teachers, it is still necessary to gain a better understanding as to what type of video (one's own or those of other teachers) is especially impactful in initial teacher education. Against this background, we conducted the intervention study Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
0
6
0
7
Order By: Relevance
“…Both Rose's 14 and our studies identified that videos allowed the students to view the content whenever suitable and as many times, to gain a more comprehensive understanding of the material. Further, Kramer et al 15 found learning with educators’ self‐made videos received a higher degree of acceptance from students. This, and ready access to the videos at any time during their simulated session was also a positive factor in engaging the students.…”
Section: Discussionmentioning
confidence: 99%
“…Both Rose's 14 and our studies identified that videos allowed the students to view the content whenever suitable and as many times, to gain a more comprehensive understanding of the material. Further, Kramer et al 15 found learning with educators’ self‐made videos received a higher degree of acceptance from students. This, and ready access to the videos at any time during their simulated session was also a positive factor in engaging the students.…”
Section: Discussionmentioning
confidence: 99%
“…They considered all three useful for enhancing their reflection on practice, with own videos positively associated with the value of seeing oneself from a distance and getting feedback from colleagues; peer videos with sharing perspectives and public videos with modelling approaches. Krammer et al's (2015) study is one of the few addressing pre-service teachers.…”
Section: Own Vs Public Videosmentioning
confidence: 99%
“…What is characteristic of both the studies in this issue and the wider literature is that the dependent or criterion variables pertain more often to teacher perceptions and thinking than to (changes in) teacher behaviour and (its impact on) outcomes in learners (cf. in this issue: Minaříková et al, 2015;Vondrová & Žalská, 2015;Mohr & Santagata, 2015;and Krammer et al, 2015).…”
Section: Overview Of Studiesmentioning
confidence: 99%